2006
DOI: 10.1128/jcm.44.1.71-76.2006
|View full text |Cite
|
Sign up to set email alerts
|

Validation of VITEK 2 Version 4.01 Software for Detection, Identification, and Classification of Glycopeptide-Resistant Enterococci

Abstract: We evaluated the ability of the new VITEK 2 version 4.01 software to identify and detect glycopeptideresistant enterococci compared to that of the reference broth microdilution method and to classify them into the vanA, vanB, vanC1, and vanC2 genotypes. Moreover, the accuracy of antimicrobial susceptibility testing with agents with improved potencies against glycopeptide-resistant enterococci was determined. A total of 121 enterococci were investigated. The new VITEK 2 software was able to identify 114 (94.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
2
10
0
1
Order By: Relevance
“…Problems in identifying enterococci with automated systems have already been reported. For instance, the VITEK 2 system failed to identify substantial numbers (9% to 37%) of E. faecium and E. faecalis isolates (1,7,12). The latter isolates were most frequently identified as E. casseliflavus/E.…”
Section: Discussionmentioning
confidence: 99%
“…Problems in identifying enterococci with automated systems have already been reported. For instance, the VITEK 2 system failed to identify substantial numbers (9% to 37%) of E. faecium and E. faecalis isolates (1,7,12). The latter isolates were most frequently identified as E. casseliflavus/E.…”
Section: Discussionmentioning
confidence: 99%
“…These organisms are sometimes difficult to cultivate and identify. The VITEK 2 system (bioMérieux, Marcy L'Etoile, France) is used worldwide for the rapid and accurate identification of gram-positive cocci, gram-negative rods, and yeasts (1,2,16,18,24) in routine clinical microbiology tests. BioMérieux has recently developed a new Neisseria-Haemophilus (NH) identification card in order to identify fastidious gram-negative and gram-variable organisms (HACEK organisms), but its performance under the conditions of a routine laboratory has not yet been evaluated.…”
mentioning
confidence: 99%
“…8 This is in accordance with the data reported in Abele-Horn et al where the VITEK 2 system correctly identified all vancomycin resistant E. faecium strains while all isolates identified with low discrimination were E. faecium LRV. 9 The E. faecium described in the present report corresponds to an LRV strain (Table 1) and this may, at least in part, explain the incorrect identification by the VITEK 2. However, this does not explain why it was classified as S. uberis.…”
Section: Discussionmentioning
confidence: 72%